Reconstruction of Abandonment and Site Restoration (ASR) Regulations to Create a Conducive Investment Climate in the Oil and Gas Sector - Sumartono sumartono; Riswadi riswadi (International Journal Labs, 2024)
The reorientation of policies related to Abandonment and Site Restoration (ASR) in the oil and gas industry is an important step to ensure environmental sustainability post-operation. This research aims to evaluate the implementation of ASR policies in Indonesia, regulated under Law No. 22 of 2001 on Oil and Gas and Government Regulation No. 27 of 2012 concerning Environmental Permits. The methodology used includes qualitative analysis of existing regulations, in-depth interviews with stakeholders in the oil and gas sector, and case studies of several companies that have implemented ASR practices. By focusing on the aspect of corporate responsibility in site recovery after operational activities, this research identifies the challenges faced by businesses in implementing sustainable ASR practices. The findings indicate the need for a review of existing regulations to align with sustainability principles and environmental protection. Recommendations for policy improvement include strengthening oversight, developing clear technical guidelines, and increasing local community engagement in the restoration process. It is expected that this policy reorientation can enhance corporate accountability and protect the environment, providing positive impacts for communities and ecosystems surrounding operational sites.